2007
DOI: 10.1007/s00221-006-0842-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of basal ganglia neurocircuitries following perinatal asphyxia: effect of nicotinamide

Abstract: The potential neuroprotection of nicotinamide on the consequences of perinatal asphyxia was investigated with triple organotypic cultures. Perinatal asphyxia was induced in vivo by immersing foetuses-containing uterine horns removed from ready-to-deliver rats into a water bath for 20 min. Sibling caesarean-delivered pups were used as controls. Three days later tissue from substantia nigra, neostriatum and neocortex was dissected and placed on a coverslip. After a month, the cultures were processed for immunocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 71 publications
3
33
0
4
Order By: Relevance
“…In a previous study (Hosamani and Muralidhara 2009), we observed that ROT-induced motor deficits in Drosophila was prevented by BM via restored antioxidant function and protection against oxidative damage with implications for neuroprotection of basal ganglia neurons. Experimental data have shown that the basal ganglia area in the brain is vulnerable to damage during brain development (Marti et al 1997;Klawitter et al 2007). Partial or complete degeneration of the dopaminergic network is found in several childhood conditions such as hypoxicischemic encephalopathy (Rutherford et al 2005), iron metabolism disorders (Hartig et al 2006), organic acidurias (Okun et al 2002), and several forms of mitochondrial diseases (Di Filippo et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study (Hosamani and Muralidhara 2009), we observed that ROT-induced motor deficits in Drosophila was prevented by BM via restored antioxidant function and protection against oxidative damage with implications for neuroprotection of basal ganglia neurons. Experimental data have shown that the basal ganglia area in the brain is vulnerable to damage during brain development (Marti et al 1997;Klawitter et al 2007). Partial or complete degeneration of the dopaminergic network is found in several childhood conditions such as hypoxicischemic encephalopathy (Rutherford et al 2005), iron metabolism disorders (Hartig et al 2006), organic acidurias (Okun et al 2002), and several forms of mitochondrial diseases (Di Filippo et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…iNOS greatly increases NO concentrations, which leads to peroxynitrite formation (Ikeno et al 2000). Another group showed decreased striatal nNOS-positive cells in organotypic cell cultures made 3 days after PA, accompanied by PA-related increases in nNOS-expressing cells in the substantia nigra, a region that normally has lower nNOS activity than the striatum (Klawitter et al 2006; Klawitter et al 2007). In the cerebellum, the coupling between increased neuronal activity and local blood flow relies almost exclusively on NO (Rancillac et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The newborn brain is especially vulnerable to this type of insult due to its relatively low antioxidant levels (McQuillen and Ferriero 2004; Shim and Kim 2013). The extent of excessive NO production is dependent on the severity/duration of asphyxia, with variability across different neuron types and nervous system locations (Dorfman et al 2009; Klawitter et al 2007). Nitrotyrosine—a product of peroxynitrite and proteins—was present in the brain tissue of human NE infants at autopsy (Groenendaal et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of extra energy for the reestablishment of homeostasis might compete with the demands required for circuitries and synapsis consolidation [55]. Several studies using the Swedish experimental model have reported distinct alterations induced by PA such as thickening of both pre- [32] and postsynaptic densities [2429, 50]; protein misfolding, aggregation, and ubiquitination [2429]; interruption of postnatal neurogenesis [58]; reduction in neurite length and branching [59, 60]; myelination deficits [63]; and modifications in the levels of synapsin [52, 60] and neurotrophic factors [61]. Some researchers have suggested the existence of plastic changes in an attempt to counterbalance neuronal loss [29, 32, 52, 57].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore dopamine agonists might have neuroprotective potential via facilitation of postnatal neurogenesis and restoration of damaged circuitries [58]. Certainly, in vitro studies revealed a selective decrease in the number, neurite length, and branching of dopamine neurons as a consequence of PA [59]. Likewise a reduction in neurite length and branching was observed in the hippocampus 1 month after PA along with reduced expression of pre- and postsynaptic markers (resp., synaptophysin and postsynaptic density protein 95, PSD95) [60].…”
Section: Effects Of Experimental Perinatal Asphyxia On Synaptic Ormentioning
confidence: 99%